Grey Literature in Health Science Libraries and Indian Institute of Technology Libraries - Sharma, Jagdish; Nandan, Poonam (Journal of Information and Knowledge, 2020)
Background: The use of Grey Literature (GL) is recognized and increasing across various disciplines. Accordingly, librarians collect, and organize such material. Objectives: To know the perceptive of librarians in Health Science disciplines and Indian institutes of technology (IITs) about user behaviour in respect of GL and how librarians are managing the same for effective use. Methods: Fifteen HSL and fourteen IITs were approached through Google forms-based questionnaire to participate in a survey. The librarians having at least ten years of experience shared their opinion and observations. Eight librarians of IITs and six librarians from health science libraries responded to the survey. Discussion & Conclusion: The most common method of GL acquisition in both group of libraries is to receive requests from students, faculty or from the management. Library professionals from both types of institutes observed that postgraduate/PhD students are the highest users of the GL such as theses and conference proceedings. It is observed that end users in IITs prefer to browse the web type facilities, whereas clinicians prefer to visit the library or interact with library professionals.